Examining the Translation and Validation of the Persian Version of Assistive Technology Device Predisposition Assessment in Adults With Disabilities - Soheila Seyedi; Kianoush Abdi; Mehdi Basakha; Samaneh Hosseinzadeh (Journal of Rehabilitation)
Objective Assistive technology is an effective tool for enhancing the participation and activity of individuals with disabilities. A key factor in the successful prescription and use of this technology is the alignment between users’ needs and preferences and the features of the assistive technology. The assistive technology device predisposition assessment tool, based on the International Classification of Functioning, Disability, and Health (ICF), simultaneously evaluates the individual, environment, and assistive technology. Accordingly, this study determines the psychometric properties of the Persian version of this tool among Persian-speaking clients of welfare centers in Ardabil Province, Iran. Materials & Methods This was a methodological study conducted in two phases. The first phase was the translation and adaptation of the tool into Persian. Initially, the English version of the tool was translated by experts in the English language and rehabilitation, with permission from the designer. Two other specialists then back-translated the translation into English. The second phase was the psychometric evaluation of the tool. The tool included 66 items across four domains (function, activity and participation, psychological-social characteristics, and device form). Content and face validity were assessed using feedback from rehabilitation and health specialists as well as individuals with disabilities, and the content validity index (CVI) and content validity ratio (CVR) were calculated. The tool was completed by 330 adults with disabilities who were using assistive technology, selected through a quota sampling method. Construct validity was evaluated via factor analysis, internal consistency was assessed using the Cronbach α method, and test-retest reliability was calculated using intra-class correlation. Results The tool was finalized without significant modifications by translators after the process of translating from Persian to English and ensuring cultural adaptation. The content validity of the tool was confirmed with a CVI of 0.95 and a CVR of 0.94. The internal consistency of the questions in the activity and participation sections, as well as the device form, was found to be satisfactory, with the Cronbach α ranging from 0.807 to 0.822. Test-retest reliability across all items was reported to be >0.9. The study was conducted with the participation of 330 individuals, 57.8% of whom were male. Conclusion The Persian version of the assistive technology device prerequisite assessment tool is valid and reliable. It can be used to evaluate the alignment between individual needs and assistive technology, as well as to assess the outcomes of rehabilitation services for Persian-speaking adults with disabilities.